Diversifikasi Produk Olahan Buah Pala (Myristica fragrans) di Desa Sukadamai - Syifa Aulia; Sugeng Heri Suseno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Diversification of products processed nutmeg can increase added value, the income and provideadvantages for nutmeg farmers and industrial. One of the home industry in Sukadamai Village isdeveloping products based on nutmeg meat into a nutmeg juice that has a lot of health benefits. Thisis aimed to determine the process of diversification of nutmeg fruit processing and analyze theadvantages of Pala home industry. Observations were held in Sukadamai Village, Dramaga SubDistrict, Bogor Regency, West Java province, 22 February 2020. The methods used in this activityare by conducting interviews to the informant regarding the making process and conducting a profitanalysis. The observation shows that the diversification of nutmeg fruit can be generated that utilizes100 kg nutmeg fruit meat in a single production. The results of economic analysis of nutmeg juicehave an R/C ratio of 1.95, which means the industry is profitable.